Meningkatkan Hasil Belajar Murid Melalui Metode Diskusi pada Mata Pelajaran Pendidikan Kewarganegaraan Tentang Menghargai dan Menaati Keputusan Bersama Kelas V Sekolah Dasar Negeri 221 Bulu Dua Kabupaten Soppeng - Andi Baso; Mardiana Mardiana (JED (Jurnal Etika Demokrasi), 2017)
The main problem in this research is how to apply the discussion method to improve the learning outcomes of Civic Education on Grade V students of SD Negeri 221 Bulu Dua District Marioriwawo Kabupaten Soppeng. This type of research is Class Action Reaserch which consists of two cycles where each cycle is held twice a meeting. The research procedure includes planning, action implementation, observation and reflection. Subjects in this study were students of class V SD Negeri 221 Bulu Dua District Marioriwawo Soppeng regency as many as 14 people. The results showed that in the first cycle students' level of satisfaction on the average material 79.64 or an increase of 10.35 from the results of initial tests taken from schools where pupil mastery of the material on average 69.29. While in cycle II obtained data that student mastery level average of 93,57 or increase 13,93 from result of formative test at cycle I where its material mastery average 79,64. The results obtained by students in cycle II is 92.86% or 13 students get the value of ≥ 70, seen from students who are categorized as very high amounted to 3 people with a percentage of 21.44%, while the high categorized students as many as 8 people with a percentage of 57, 14%. And accompanied by the achievement of all indicators in teacher and student observation.Keywords: Learning Outcomes, Discussion, Students.